FRI0544 Non-Structural Factors Associated with Current and New Foot Pain: Data from the Tasmanian Older Adult Cohort Study. (9th June 2015) - Laslett, L.L.; Menz, H.; Cicuttini, F.; Jones, G.
Abstract : Background: Foot pain is common, and associated with decreased ability to undertake activities of daily living, problems with balance and gait and increased risk of falls. However, few population-based studies have examined factors associated with foot pain in the general community. Objectives: To assess non–structural factors associated with foot pain both cross sectionally and longitudinally over 5 years, in a community dwelling sample of older adults. Methods: Longitudinal population-based cohort study of randomly selected older adults (n=1040). Foot pain (yes/no) was assessed by questionnaire at baseline and after 5 years of observation. Potential correlates included demographic factors (age, sex, cigarette smoking), diabetes, anthropometry (weight, BMI, waist/hip ratio), lower leg strength (leg strength using dynamometer (kg), leg lean mass (kg), leg muscle quality (leg strength/leg lean mass)), steps per day (as assessed by pedometer), pain in the neck, shoulder, back, hands, hips, knees (all yes/no), the Psychological Wellbeing scale of Assessment of Quality of Life questionnaire (AQoL), and serum vitamin D. Logistic regression was used for cross-sectional associations with prevalent foot pain, and negative binomial regression for longitudinal associations with new foot pain. Results: Participants were aged 50-80 years (mean 63 years), 49% male, mean BMI 27.8±4.7 at baseline. Prevalence of foot pain at baseline was 37.7% (95% CI 34.8 to 40.6%), incidence of new pain after 5 years was 19.6% (95% CI 16.1 to 23.1%). Persons with prevalent foot pain were more likely to be male, have poorer leg strength, higher weight and BMI, fewer steps per day, poorer psychological wellbeing, and have pain at more sites (other than feet). New foot pain was associated with male sex and the following at baseline: greater BMI and hip circumference, poorer leg muscle quality (leg strength/lower leg lean mass), poorer psychological wellbeing, and number of non-foot sites with pain; all p<0.05. Greater weight, poorer leg strength, pain at 3 or more sites, and poorer psychological quality of life were all associated with increased odds of foot pain at baseline (Table ). Similar factors were associated with increased risk of new foot pain developing over 5 years in people reporting no foot pain at baseline: greater weight, poorer leg strength and pain at 3 or more sites (Table ). Psychological wellbeing was not an independent predictor of new knee pain after 5 years. Conclusions: Weight, poorer leg strength, and pain at other sites are consistently associated with prevalent foot pain and predict new foot pain. Poor psychological wellbeing is associated with existing foot pain. This suggest that weight reduction, improving leg strength and taking a global approach to the treatment of pain may reduce the prevalence and incidence of foot pain in older adults. Disclosure of Interest: None declared